Sharing a Government. Issue 6 (29th November 2019) - Ventura, Jaume
Abstract: This paper develops a simple theoretical framework to study a set of regions, each with its own regional government, who share a union or central government. These governments must decide whether to implement or discard a large number of projects that produce local benefits for the region that implements them, and externalities for the rest of the regions. Conflict or disagreement arises since different regions value projects differently. The classic assignment problem consists of deciding who decides these projects, either the union or the regional governments. It is well known that regional governments are insensitive to externalities. The key observation here is that the union government is insensitive to local benefits. Thus, each government maximizes only a piece of the value of projects, and disregards the other one. This observation leads to simple and clear rules for solving the assignment problem.